(untitled) (Scientific journal of the Fergana State University, 2025)
The alkaloid composition of Allium karataviense, including its bulb, stem, leaf, flower, and seeds, was investigated using qualitative analysis methods. The presence of alkaloids in the leaves and stems was confirmed through tests with tannin solution and silicotungstic acid solution. Qualitative reactions for alkaloids in the flower and bulb were conducted using Bushard reagent, Dragendorff reagent, tannin solution, and silicotungstic acid solution. It was determined that the influence of tannin solution on qualitative reactions was relatively higher.